A new approach in designing Arabic language practices for primary school students in Malaysia - Muhammad, Norasmazura; Raja Sulaiman, Raja Munirah; Hashim, Marzidah; Usop, Mohd Puzhi; Abd. Hamid, Mohd Azrul Azlen; Selamat, Nita Fauzee (2014)

(untitled)
This is a project conducted to design Arabic language practices for primary school students in Malaysia. The main objective of this project is to provide the latest design of Arabic language practices which is specially designed to promote self-learning culture among the primary school pupils. The project was completed through different phases, beginning with data collection, data analysis, designing process and editing. The project was successfully conducted and six sets of Arabic language exercise books were produced and published by a local publisher in year 2012.